Renoprotective Effect of the L/N-Type Calcium Channel Antagonist Cilnidipine on Puromycin Aminonucleoside-Induced Nephrosis in Rats - Takashima, Kayoko; Nishiyama, Chizuru; Arisaka, Nobuhiko; Takahashi, Tetsuaki; Souma, Shinji; Tsuda, Miyuki; Hayashi, Morimichi; Kasahara, Hiroko; Kodama, Hirokazu; Tamura, Tora; Murakami, Makoto; Kuroda, Junji; Sato, Fumiyasu (Arzneimittelforschung, 2009)
The renoprotective effect of cilnidipine ((±)-2-methoxyethyl 3-phenyl-2(E)-pro-penyl 1,4-dihydro-2,6-dimethyl-4-(3-ni-trophenyl)-3,5-pyridinedicarboxylate, CAS 132203-70-4), a L/N-type calcium channel antagonist, on puromycin aminonucleoside (PAN)-induced nephrosis was investigated in rats.In the Experiment I, rats were given an intravenous injection of PAN (70 mg/kg). Cilnidipine (3 mg/kg/day) and enalapril (CAS 75847-73-3, 5mg/kg/day) were administered orally from 6 days after treatment with PAN (day 6) to day 26, and urinary analysis was performed on days 9, 15, 20 and 27. In the Experiment II, nephrosis was also induced by intravenous injection of PAN (70 or 100 mg/kg) in rats which were treated with cilnidipine and enalapril from days 6 to 10. Systolic blood pressure was measured on day 7 and urinary analysis was performed on day 10. On day 11, serum was collected and the kidneys were removed for immunofluorescence staining for nephrin and podocin proteins.In PAN-treated rats, the daily urinary protein excretion was dramatically elevated on day 5, reached a peak on day 9 and gradually returned to a normal level from days 15 to 27. Cilnidipine (3 mg/kg/day) significantly suppressed the increase in proteinuria on day 9 and also improved the decrease in creatinine clearance without evident effect on the blood pressure. Furthermore, the elevations in serum total cholesterol and triglyceride tended to be suppressed by cilnidipine. The expression of nephrin and podocin proteins in PAN-treated rats showed the granular pattern in the glomeruli, while the intensity of staining seemed to be dependent on the urinary protein excretion level in the cilnidipinetreated rats.The results obtained in this study suggest a renoprotective effect of cilnidipine in PAN-induced nephrosis in rats.
Keywords: CAS 132203-70-4; Calcium antagonist, L/N-type; Cilnidipine, renoprotective effect; Nephrosis, puromycin aminonucleoside-induced